Parenting skills : exploring the success stories of Ibu Mithali's parenting style and nurturance of their children - Jamiah Manap (Institute of Education, International Islamic University Malaysia, 2013)
The research aims to explore the experiences of Ibu Mithālī in nurturing their children. Ibu Mithālī is a national award bestowed upon exemplary mother to recognize their accomplishment in raising the children. Three main research questions were employed for this research: 1) How did Ibu Mithālī show good role model in nurturing their children, 2) How did Ibu Mithālī develop resilience among their children, and 3) How did Ibu Mithālī nurture their children. The research drew upon the Grounded Theory approach in qualitative research method in order to answer the research questions. An in-depth and semi structured interview based on al-Ghazali's Model of Parenting Skill Attributes were also conducted with four Ibu Mithālī and eight of Ibu Mithālī's children. The interview locations revolved around Johor, Kuala Lumpur, Selangor, Kedah and Kelantan. Meanwhile the data collection method engaged with document analysis, and observation.The research discovered that, Ibu Mithālī demonstrated positive role model in the relationship with Allah through the culture of knowledge, strong faith, prayer, fasting, recite Qur'ān and good ethics of conduct. Ibu Mithālī developed resilience among their children through the consolidation of the relationship between their children with Allah and others. Relationship with Allah encompassed prayer, fasting, reciting the Qur'ān and inculcating knowledge culture. Relationship with others covered religious education, generosity, building and maintaining the relationship, and being conflict resolving. Ibu Mithālī also applied seven methods in nurturing children: permissible earning, showing affection, keeping the tie of relationship, being fair, disciplining their children, fulfilling their needs and developing the children. Research also discovered that positive environment or Bi'ah Ṣāleḥah was the emerging factor that significantly contributed to the success Ibu Mithālī and their children. Conducive environment included positive socio-cultural environment, positive minded people and a supportive spouse. The research also established the Ibu Mithālī's Model of Parenting Skill and Ibu Mithālī's Principle of Parenting. In summary, Ibu Mithālī's are the benchmark of the Muslim parenting skills in Malaysia. Their skills should become references and guidelines in enhancing the quality of parenting